2001
DOI: 10.1074/jbc.m009148200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of the First F3 Domain from Chicken Collagen XIV Affects Cell Adhesion and Heparin Binding

Abstract: The N terminus of chicken collagen XIV is subject to alternative splicing. The longer isoform contains a fibronectin type III (F3) domain at its N terminus, whereas the shorter isoform is lacking this domain. Alternative splicing of the F3 domain is developmentally regulated. At early embryonic stages, both isoforms are expressed, whereas after hatching only the longer isoform is expressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The results of these noteworthy biological effects of CXIV are in accord with published data on CXIV as a cell adhesion molecule. Thus we and others showed that the first FN-III domain and its immediate carboxyl-terminal extension (equivalent to fragment Gln 29 -Pro 154 ) mediates attachment of hematopoietic and mesenchymal cells (14,26,27). In other reports, a 16-kDa aminoterminal fragment of rat CXIV similar to the recombinant human CXIV fragment Gln 29 -Pro 154 used in our study was identified as a potent neu- trophil chemoattractant (15).…”
Section: Discussionmentioning
confidence: 81%
“…The results of these noteworthy biological effects of CXIV are in accord with published data on CXIV as a cell adhesion molecule. Thus we and others showed that the first FN-III domain and its immediate carboxyl-terminal extension (equivalent to fragment Gln 29 -Pro 154 ) mediates attachment of hematopoietic and mesenchymal cells (14,26,27). In other reports, a 16-kDa aminoterminal fragment of rat CXIV similar to the recombinant human CXIV fragment Gln 29 -Pro 154 used in our study was identified as a potent neu- trophil chemoattractant (15).…”
Section: Discussionmentioning
confidence: 81%
“…One of these splices away the first FN III domain on the N terminus of the protein (Imhof and Trueb, 2001). Interestingly, the intron sequences reported also were similar in size between the two species.…”
Section: Genomic Organization Of the Col14a1 Genementioning
confidence: 83%
“…Exonyintron size for human gene (Imhof and Trueb, 2001). The domains coded for by the different exons are indicated.…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%
“…2 for types IX, XII, and XIV. These three collagens can be alternatively spliced to yield short and long variants (Svoboda et al 1988; Gerecke et al 1997; Imhof and Trueb 2001) that might confer different properties to the fibrils in tissues. Type XIV collagen is also a fibril diameter regulator in early stages of fibrillogenesis (Ansorge et al 2009).…”
Section: Collagens Associated With Banded Fibrilsmentioning
confidence: 99%